Design Considerations for Patient Portal Adoption by Low-Income, Older Adults - Latulipe, Celine; Gatto, Amy; Nguyen, Ha T; Miller, David P; Quandt, Sara A; Bertoni, Alain G; Smith, Alden; Arcury, Thomas A (Proceedings of the SIGCHI conference on human factors in computing systems. CHI Conference, 2015)
This paper describes the results of an interview study investigating facilitators and barriers to adoption of patient portals among low-income, older adults in rural and urban populations in the southeastern United States. We describe attitudes of this population of older adults and their current level of technology use and patient portal use. From qualitative analysis of 36 patient interviews and 16 caregiver interviews within these communities, we derive themes related to benefits of portals, barriers to use, concerns and desired features. Based on our initial findings, we present a set of considerations for designing the patient portal user experience, aimed at helping healthcare clinics to meet U.S. federally-mandated 'meaningful use' requirements.